Temporal delay discounting in acutely ill and weight-recovered patients with anorexia nervosa. Issue 6 (12th January 2015) - Ritschel, F.; King, J. A.; Geisler, D.; Flohr, L.; Neidel, F.; Boehm, I.; Seidel, M.; Zwipp, J.; Ripke, S.; Smolka, M. N.; Roessner, V.; Ehrlich, S.
Abstract : Background: Patients with anorexia nervosa (AN) are characterized by a very low body weight but readily give up immediate rewards (food) for long-term goals (slim figure), which might indicate an unusual level of self-control. This everyday clinical observation may be quantifiable in the framework of the anticipation-discounting dilemma. Method: Using a cross-sectional design, this study compared the capacity to delay reward in 34 patients suffering from acute AN (acAN), 33 weight-recovered AN patients (recAN) and 54 healthy controls. We also used a longitudinal study to reassess 21 acAN patients after short-term weight restoration. A validated intertemporal choice task and a hyperbolic model were used to estimate temporal discounting rates. Results: Confirming the validity of the task used, decreased delay discounting was associated with age and low self-reported impulsivity. However, no group differences in key measures of temporal discounting of monetary rewards were found. Conclusions: Increased cognitive control, which has been suggested as a key characteristic of AN, does not seem to extend the capacity to wait for delayed monetary rewards. Differences between our study and the only previous study reporting decreased delay discounting in adult AN patients may be explained by the different age range and chronicity of acute patients, but the fact that weight recovery was not associated with changes in discount rates suggests that discounting behavior is not a trait marker in AN. Future studies using paradigms with disorder-specific stimuli may help to clarify the role of delay discounting in AN.